2014
DOI: 10.7314/apjcp.2014.15.8.3625
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Analysis of Gestational Trophoblastic Neoplasia in Turkey

Abstract: The incidence was calculated to be 0.38 per 1,000 deliveries. According to the evaluated data of 364 patients, the median age at diagnosis was 31 years (range, 15-59 years). A histopathological diagnosis was present for 45.1% of the patients, and invasive mole, choriocarcinoma and PSTTs were diagnosed in 22.3% (n=81), 18.1% (n=66) and 4.7% (n=17) of the patients, respectively. Regarding final prognosis, 352 (96.7%) of the patients had remission, and 7 (1.9%) had persistence, whereas the disease was mortal for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…11 A multicenter analysis of GTN in Turkey from 2003 to 2013 reported the incidence was 0.38 per 1,000 deliveries. 12 This is understandable, since our hospital is a large-scale comprehensive hospital and settled as the GTN treatment center in northwestern of China, and more normal deliveries occurred in local hospitals because of the development of primary care.…”
Section: Discussionmentioning
confidence: 94%
“…11 A multicenter analysis of GTN in Turkey from 2003 to 2013 reported the incidence was 0.38 per 1,000 deliveries. 12 This is understandable, since our hospital is a large-scale comprehensive hospital and settled as the GTN treatment center in northwestern of China, and more normal deliveries occurred in local hospitals because of the development of primary care.…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, a study from Turkey conducted in 28-center, reported that 456 gestational trophoblastic diseases were observed in 1,173,235 births (0.38 per 1000 births) and the mean age at diagnosis was 31years. 21,22 Maternal age, previous abortion, previous HM diagnosis, ethnicity, oral contraceptive usage, intrauterine vehicle, blood group, radiation, socioeconomic status, nutrition, infertility and genetic factors have been reported in several publications. All of these factors mainly focus on maternal age and history of HM.…”
Section: Discussionmentioning
confidence: 99%
“…This finding may be explained by the modality of treatment in GTN. Although hysterectomy were necessary in some cases, the majority of GTN patients could be cured by chemotherapy alone which can preserve uterus and ovaries (Pongsaranantakul and Kietpeerakool, 2009;Seckl et al, 2010;Manopunya and Suprasert, 2012;Ozalp et al, 2014). Previous study (Pinar et al, 2012)showed that hysterectomy had negative effects on body image and self-esteem in women affected by gynecologic cancer.…”
Section: Discussionmentioning
confidence: 99%